Effect of combined treatment with insulin and metformin on 5′AMPactivated protein kinase activity in lymphocytes of diabetic patients - Sokolova, L.K.; Pushkarev, V.M.; Belchina, Y.B.; Pushkarev, V.V.; Tronko, M.D. (Доповіді НАН України, 2018)
The activity of 5′adenosine monophosphate-activated protein kinase (AMPK), controlling the energy balance of a cell, in blood cells at the combined treatment of patients with type 2 diabetes with metformin and insulin was determined by enzyme immunoassay. It has been shown that metformin increases threefold the AMPK activity in lymphocytes of patients with type 2 diabetes, compared with patients before treatment. Insulin and its analog reduced the activity of the protein kinase stimulated by metformin in the blood cells, acting as metformin antagonists. The mechanisms of drug interaction and the consequences of their antagonism are discussed.